2019
DOI: 10.3390/ma12213578
|View full text |Cite
|
Sign up to set email alerts
|

Features of the Microstructure and Chemical Compositions of Vanadium-Containing Slags Including Determination of Vanadium Oxidation Degrees

Abstract: Metallurgical vanadium-containing converter slag could be used as an alternative vanadium source. The development of a physico-chemical basis for the comprehensive processing of industrial vanadium-containing debris requires information about their elemental composition as well as the oxidation degrees of the elements and forms of compounds in order to solve two key problems: a better utilization of industrial wastes and a lowering of environment impact. This research was aimed at the development of methods to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…In previous works, we have shown the influence of the degree of oxidation and forms of compounds of elements on the manufacturability of processing the corresponding raw materials [ 41 , 42 , 43 ]. To study the mineral composition and the degree of oxidation of elements in vanadium raw materials, the following methods are described: X-ray phase analysis [ 44 , 45 , 46 ], X-ray photoelectron spectrometry [ 45 , 47 , 48 ], titrimetric [ 44 , 45 , 49 ], electrochemical methods [ 44 ], mass spectral [ 50 ], thermal analysis [ 48 ], infrared spectrometry [ 48 ], electron microscopy [ 46 , 47 ], study of the fine structure of the X-ray absorption spectrum (XAFS) [ 17 ], and nuclear magnetic resonance method [ 27 ].…”
Section: Resultsmentioning
confidence: 99%
“…In previous works, we have shown the influence of the degree of oxidation and forms of compounds of elements on the manufacturability of processing the corresponding raw materials [ 41 , 42 , 43 ]. To study the mineral composition and the degree of oxidation of elements in vanadium raw materials, the following methods are described: X-ray phase analysis [ 44 , 45 , 46 ], X-ray photoelectron spectrometry [ 45 , 47 , 48 ], titrimetric [ 44 , 45 , 49 ], electrochemical methods [ 44 ], mass spectral [ 50 ], thermal analysis [ 48 ], infrared spectrometry [ 48 ], electron microscopy [ 46 , 47 ], study of the fine structure of the X-ray absorption spectrum (XAFS) [ 17 ], and nuclear magnetic resonance method [ 27 ].…”
Section: Resultsmentioning
confidence: 99%
“…In accordance with the traditions of analytical chemistry compositions of complex oxide systems such as ores, ceramics and so on is listed for most elements in terms of oxides where oxides of polyvalent metals are given in maximal oxidation degrees. So, XRF data for vanadium compounds in slags was given for V2O5 oxide while XPS has demonstrated that it was presented only in V 2+ and V 3+ states [18]. One can see from Table 1 that XRF is enough sensitive to detect small impurities with content down to 0.003 %mass.…”
Section: Comparison Of Xrf and Sims Analytical Capabilitiesmentioning
confidence: 99%